2023
DOI: 10.3389/fphar.2023.1146651
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ferroptosis as a promising therapeutic strategy to treat cardiomyopathy

Abstract: Cardiomyopathies are a clinically heterogeneous group of cardiac diseases characterized by heart muscle damage, resulting in myocardium disorders, diminished cardiac function, heart failure, and even sudden cardiac death. The molecular mechanisms underlying the damage to cardiomyocytes remain unclear. Emerging studies have demonstrated that ferroptosis, an iron-dependent non-apoptotic regulated form of cell death characterized by iron dyshomeostasis and lipid peroxidation, contributes to the development of isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 164 publications
0
0
0
Order By: Relevance
“…Ferroptosis is a form of programmed cell death that relies on iron-catalyzed lipid peroxidation, distinguishing it from autophagy, apoptosis, and necrosis [ 27 ]. Numerous studies have demonstrated the involvement of ferroptosis in myocardial injury, including DCM [ 11 , 28 ]. Our data further substantiate the association between ferroptosis and DCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferroptosis is a form of programmed cell death that relies on iron-catalyzed lipid peroxidation, distinguishing it from autophagy, apoptosis, and necrosis [ 27 ]. Numerous studies have demonstrated the involvement of ferroptosis in myocardial injury, including DCM [ 11 , 28 ]. Our data further substantiate the association between ferroptosis and DCM.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis, an iron-dependent form of regulatory cell death, is activated in DCM and has been shown to play an indispensable role in its pathogenesis [ 10 ]. The inhibition of cardiomyocyte ferroptosis could alleviate the progression of DCM [ 11 , 12 ]. Ferroptosis is implicated in myocardial injury in type 2 diabetes mellitus (T2DM), and inhibition of retinol dehydrogenase 10 (RDH10) promotes retinol metabolism disorder, thereby promoting ferroptosis in the heart [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent insights into iron-mediated programmed cell death, or ferroptosis, have highlighted its crucial role in various pathophysiological conditions [ 5 ], including cardiomyopathies linked to sepsis [ 6 ]. Ferroptosis is characterized by iron accumulation and lipid peroxidation, leading to cell membrane rupture, thus distinguishing it from traditional cell death mechanisms [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is characterized by iron accumulation and lipid peroxidation, leading to cell membrane rupture, thus distinguishing it from traditional cell death mechanisms [ 5 ]. Recent studies have elucidated the complex interplay between iron dysregulation and oxidative stress in precipitating ferroptosis within cardiac tissues, significantly contributing to the intricate pathology of SICM [ 6 ]. Targeted modulation of cellular processes, particularly through agents like microRNA-130b-3p and the PARP inhibitor Olaparib, has shown potential in mitigating ferroptosis and improving clinical outcomes in SICM models [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%